Mineral decline due to modernization of food habits. (1st January 2016) - Henry, Christiani Jeyakumar; Bi, Xinyan; Lim, Joseph; Lau, Evelyn
Highlights: A minor change in dietary habits leads to a reduction in micronutrients intake. Both head and skeleton have higher calcium than cleaned body of anchovy. Entrails are observed to be a major contributor to zinc and iron. Abstract: Calcium and other micronutrients are essential for health and well-being. Dairy products are the main sources of calcium in western countries. In most regions of Asia, the consumption of these products is limited due to the lactose intolerance and costs. A major contributor to the micronutrients intake in this region is the consumption of small fish, such as anchovies. Traditionally, dried anchovies are consumed as a whole body. Recently, an increasingly popular method of eating anchovies has been to eat it in a cleaned, eviscerated form. This brief communication highlights how "modernization" of food habits may have unintentional nutritional consequences. A minor change in the dietary habits of eating cleaned anchovies may lead to a reduction in micronutrients intake. This reinforces the need for caution when we modernize our traditional eating habits.